On a complete topological inverse polycyclic monoid - Bardyla, S.O.; Gutik, O.V. (Carpathian Mathematical Publications, 2016)
We give sufficient conditions when a topological inverse λ-polycyclic monoid P_λ is absolutely H-closed in the class of topological inverse semigroups. For every infinite cardinal λ we construct the coarsest semigroup inverse topology τ_mi on P_λ and give an example of a topological inverse monoid S which contains the polycyclic monoid P_2 as a dense discrete subsemigroup.